Normative Review of Legal Protection for Athletes with Achievements in Lampung Province - Siagian, Debora Shintiya; Simarmata, Ocniel Juandi; Alfian, Angga (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The phenomenon of sports in Indonesia, since the time of the kings before colonization until now, is very important to be studied for the development of sports in the current context and future context. The sport of hunting for example, which later developed into archery is a tangible result of the development of the sport. Nowadays when we hear the word "sport" or "sport" that comes to mind we are athletes. Even though many sports players other than athletes such as coaches, referees, and administrators of sports organizations who in carrying out their profession, must be willing to sacrifice their time, energy, mind, and even family to be able to provide maximum achievements in order to make the name of the nation and country proud. One of them is athletes, who have to sacrifice time, energy, material, even have to be willing to be far away and separated from their families in order to strive for achievements in order to raise the red and white flag on the highest pole in every race. Therefore, it is undeniable that athletes also expect material appreciation from the government that can support their lives in the future. In addition to the welfare provided, every sports player is entitled to legal protection from the government. Protection of sports players is needed based on applicable laws and regulations. The National Sports System Law, Article 55 paragraph (3) explains that "Every professional sportsperson has the right to (a) be accompanied by, inter alia, managers, coaches, medical personnel, psychologists, and legal experts, (b) participate in championships at all levels in accordance with the provisions, (c) obtain coaching and development from the parent sports organization, professional sports organization, or functional sports organization, (d) obtain a reasonable income". Then Article 64 explains that sports personnel in carrying out their profession have the right to obtain: (a) coaching, development, and skill improvement through training, (b) safety guarantees, career advancement, welfare services, legal aid, and/or awards.